Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1155/2017/2796054
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of Open Fractures Contaminated by Seawater: Infection, Pathogens, and Antibiotic Resistance

Abstract: Aims. In this work, the main objectives were to investigate the clinical characteristics and bacterial spectrum present in open fractures contaminated by seawater. Methods. We conducted a retrospective cohort study and included all patients with open fractures from 1st January, 2012, to 31st December, 2015, in our hospital. Patients were grouped based on the presence of seawater contamination in wounds. We compared the infection rate, bacterial spectrum, and antibiotic resistance between the two groups. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…25 EDTA was more effective than NS solution in a rat wound model infected with seven of the most commonly isolated pathogens, which represent more than 90% of causative strains. 33 Furthermore, we showed that EDTA solution was also superior to castile soap, benzalkonium chloride, and bacitracin. PJI remains a great challenge to the orthopaedic community.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…25 EDTA was more effective than NS solution in a rat wound model infected with seven of the most commonly isolated pathogens, which represent more than 90% of causative strains. 33 Furthermore, we showed that EDTA solution was also superior to castile soap, benzalkonium chloride, and bacitracin. PJI remains a great challenge to the orthopaedic community.…”
Section: Discussionmentioning
confidence: 91%
“…36 Pathogens such as MRSA, ESBL-EC, MRPA, VRE, MRAB, MRE, and MRPM have been found to be the most frequent drug-resistant strains isolated from infected open fractures. 33 Although many novel antimicrobials have been established in recent decades, management of wound infection by these bacteria has been increasingly challenging. 37 Irrigation and debridement of wounds remains the cornerstone to eliminating such infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the physical properties of seawater, such as its hypertonic nature, high sodium level, alkalinity, and low temperature, directly affect the species composition. The most commonly observed bacterial infections following an open fracture on land are caused by Pseudomonas aeruginosa , Acinetobacter baumannii, Enterobacter , and methicillin-resistant Staphylococcus aureus, none of which exist in wounds soaked in seawater [ 7 ]. These differences may be attributed to two factors: first, bacterial infections may be associated with differences in the causative species and their quantity, virulence, and invasiveness; second, people living on land for a long time have different body reactions to marine bacteria, in terms of the time, degree, and scope of infection, among others.…”
Section: Introductionmentioning
confidence: 99%
“…With the extensive use of high-tech weapons, especially precision-guided missiles on the battlefield, the trauma and burns caused by high-energy explosion in naval battle have become the most important and challenging healthcare issues (Zhu et al, 2017;Chen et al, 2019). In modern high-tech naval warfare, the unavoidable exposure of open traumas to seawater with high salt, high sodium, and a high abundance of pathogenic bacteria, especially gram-negative bacteria, can cause serious infections and wound-repair difficulties (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%